Identifying the Factors for the Adoption of Expert-Based Intelligent Decision Support Systems by Small and Medium Enterprise Entrepreneurs in India - Basheer Khan, Abdul (Digital Repository of Theses, 2024)
The thesis aims to identify the factors for the adoption or Expert based of knowledge based decision support system, a model proposed by Tariq and Rafi in 2012 using Technology-Organisation-Environment framework by Small and Medium enterprises in India. The data was collected from 508 participants using simple random sampling from different parts of India. Structural equation modelling technique was used to derive results from the raw data. Hypothesis were developed on seven parameters and the analysis found that only two parameters to be significant in the study, namely the complexity factors and environment factors. It explains that those organisations that are willing to adopt the technology, they are weary of the negative impact the technology has brought. They feel that they will adopt this technology sooner or later or they will be forced to adopt this technology but the stakeholders should first get rid of the complexity factors and external factors to enable the technology’s adoption. Keywords Factors of adoption, Intelligent decision support system, Tehnology-Organisation-Environment framework, Small and medium enterprises, India.